OP0227 Features and longitudinal analysis of systemic sclerosis patients with inappropriate exercise-induced increase in pulmonary artery pressure estimated by echocardiography. (23rd January 2014) - Codullo, V.; Caporali, R.; Cuomo, G.; D'Alto, M.; Pazzano, A.S.; Camporotondo, R.; Fusetti, C.; Borgogno, E.; Montecucco, C.; Valentini, G.
Abstract : Background: Patients with Systemic Sclerosis (SSc) are at risk of developing pulmonary hypertension (PH). The role of exercise testing in predicting this severe complication is still debated. In SSc, a subset of patients show a response to exercise with particularly high (≥48 mmHg) pulmonary artery systolic pressures (PASP) 1 . Objectives: To describe baseline characteristics of SSc patients with an echocardiographic inappropriate response to exercise and determine its predictive value for the development of PH in SSc. Methods: Patients with SSc in NYHA class I-II and a peak tricuspid regurgitant jet velocity <3 m/s at rest echocardiography consecutively admitted to 2 Rheumatology Units were enrolled. Clinical characterisation of SSc patients was performed according to EUSTAR recommendations. The risk prediction score (RPS) based on clinical parameters was calculated 2 . Baseline and stress echocardiography were assessed using similar commercial equipments and a standard protocol 1 . Right heart catheterisation confirmed PH if suspicion arose during follow-up. Data were analysed with SPSS software. Results: A total of 170 patients had complete data at the end of follow-up. According to the previously defined cut-off of exercise PASP (ePASP), SSc patients were divided into those with a value below (group 1, n=149) or above 48 mmHg (group 2, n=21). Patients in both groups had comparable features concerning sex, cutaneous subset and autoantibody profile. There was no statistically significant difference in age, disease duration, mRSS, FVC (% pred), DLCO (%) or DLCO/VA (%). Presence of interstitial lung disease tended to be more frequent in group 2 than in group 1 (62% vs 37%, p=0.053). RPS values also did not discriminate between groups (3.4±0.9 vs 3.2±0.8). After a mean of 32±0.7 months, 165 (96%) were still in follow-up, 5 (3%) patients had died (all SSc-related deaths, but none including PH). Six patients (3.5%) developed PH confirmed at right heart catheterisation. Mean DLCO (p<0.01), DLCO/VA (p<0.05), RPS (<0.05), ePASP (p<0.05) or the difference between ePASP and PASP at rest (DPASP) (p<0.001) measured at the study enrolment were significantly different in patient who subsequently developed PH versus those free of this complication at the end of follow-up. Univariate PH-free survival was significantly lower in patients with an ePASP ≥48 mmHg (p<0.05) or in those in the 5th quintile of RPS (p<0.01), but at the multivariate Cox Regression, adjusting for potential confounders, only the value of DPASP (5 mmHg increase, HR 3.4 (1.4-8), p<0.01) and being in the highest quintile of RPS (HR 9.3 (1.4-63.7), p<0.05) significantly predicted survival. Conclusions: The subset of SSc patients with an inappropriate increase in PASP detected by stress echocardiography cannot be distinguished by any of the disease specific features, including a recently described and validated RPS. The difference between PASP values at rest and under stress is predictive of subsequent development of PH independently of other known predictors based on clinical observations. References: D'Alto M, et al. Heart 2011;97:112. Meune C, et al. Arthritis Rheum 2011;63:2790. Disclosure of Interest: None Declared